Hepatic hydatid cyst, laparoscopic management. Case report - Campos-Guzmán, Robert William (2015)
We report a case of male patient of 32 years old; with a history of thoracic surgery for hydatid cyst at 9 years of age; admission was at the general surgery Service of the Hospital II Lima Norte Callao Luis Negreiros Vega, with a history of illness of 1 year, referring abdominal pain oppressive predominance of the upper abdomen, especially on right upper quadrant. Refers concomitantly history of previous surgery in thoracic region and positive epidemiological history. After clinical evaluation by the staff of surgery, outpatient clinic and the observation and reporting of CT in which well-defined lesions in segment IV and V multicystic appearance and lesser sac showing peripheral enhancement it is observed after administration contrast; associated with positive Western Blot, surgical treatment is decided. Laparoscopic Surgery was performed consisting of cyst aspiration drainage and washing the interior with hipersodio (20% ClNa) and placement of laminar drain was done. Presented a postoperative biliary fistula that was resolved in five weeks, beginning of oral tolerance on the first postoperative day and liver function controls within normal ranges discharge was performed four days after surgery.